2000
DOI: 10.1200/jco.2000.18.8.1614
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Therapy of Stage III and IV Malignant Melanoma Using Granulocyte-Macrophage Colony-Stimulating Factor

Abstract: GM-CSF may provide an antitumor effect that prolongs survival and disease-free survival in patients with stage III and IV melanoma who are clinically disease-free. These results support institution of a prospective, randomized clinical trial to definitively determine the value of surgical adjuvant therapy with GM-CSF in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
142
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 232 publications
(150 citation statements)
references
References 30 publications
6
142
1
1
Order By: Relevance
“…Other possible contributors to this lack of significant benefit include lack of efficacy, pre-existing immune status of patients, immunologic response to GM-CSF, development of neutralizing antibodies to GM-CSF, effects of GM-CSF on suppressor elements (such as myeloid-derived suppressor cells), and possible suboptimal dose and/or duration of treatment. 6,7,9 The greater effect on OS than on RFS seen in other studies [6][7][8] was not seen in this study. In HLA-A2-positive patients, the median RFS was 1.7 months longer in patients who received PV versus PV placebo (11.5 v 9.8 months; 17.3% improvement), which was less than the expected improvement (3 months; 33% improvement) and not statistically significant.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Other possible contributors to this lack of significant benefit include lack of efficacy, pre-existing immune status of patients, immunologic response to GM-CSF, development of neutralizing antibodies to GM-CSF, effects of GM-CSF on suppressor elements (such as myeloid-derived suppressor cells), and possible suboptimal dose and/or duration of treatment. 6,7,9 The greater effect on OS than on RFS seen in other studies [6][7][8] was not seen in this study. In HLA-A2-positive patients, the median RFS was 1.7 months longer in patients who received PV versus PV placebo (11.5 v 9.8 months; 17.3% improvement), which was less than the expected improvement (3 months; 33% improvement) and not statistically significant.…”
Section: Discussioncontrasting
confidence: 52%
“…5 Early clinical trials support the possible benefit of GM-CSF as adjuvant therapy for melanoma. Spitler et al 6 reported longer overall survival (OS) of 48 patients with stage III to IV melanoma treated for 1 year with adjuvant GM-CSF compared with historical controls (median OS, 37.5 v 12.2 months; 2-year survival, 64% v 15%). A subsequent single-arm trial in 98 patients with stage II, III, or IV melanoma evaluated GM-CSF for 3 years and demonstrated 5-year melanomaspecific survival rates of 67% and 40% among patients with resected stage III and IV disease, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The strong induction of GM-CSF production by CC-5013 in all nine patients is further evidence of immune activation and is likely to lead to the stimulation and increased functional capacity of monocytes/ macrophages and dendritic cells (Armitage, 1998), thereby potentially boosting the presentation of tumour antigens. The clinical use of recombinant GM-CSF as a cancer immunotherapy has led to reports demonstrating its benefits in the treatment of patients with melanoma (Armitage, 1998;Spitler et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human GM-CSF is used clinically to treat a variety of hematopoietic disorders, including reducing the severity of chemotherapy-induced neutropenia, accelerating hematopoietic recovery following bone marrow transplantation and mobilizing blood progenitor cells for transplantation (1,2). Recombinant GM-CSF also has shown promise as a treatment for Crohn's disease and as an adjuvant therapy for melanoma (3,4). A limitation of current GM-CSF products is the fact that GM-CSF has a short circulating half-life (1,2) and must be administered to patients by daily injection for optimal effectiveness.…”
Section: Introductionmentioning
confidence: 99%